Four lines of compliance-protection of an industrial enterprise - Kobielieva, Tetiana (My University, 2019)
In the process of improving the corporate governance system, the need to create a compliance unit is conditioned by the adoption of a corporate strategy. In particular, an effective compliance control service, including compliance risk assessment, is important to achieve the strategic goals and objectives of the corporation (for example, when acquiring or selling a business, the initial and subsequent placement of stocks and bonds in foreign capital markets, obtaining foreign loans, attracting foreign loans, attracting strategic foreign investors). Hence the increased interest on the part of practitioners to analyze the impact of compliance control functions on the implementation of corporate governance principles, as well as the identification of those subject areas of corporate management that require constant compliance support. The article proposes the creation of a compliance service on the basis of four lines of compliance protection. Recommendations are given on the conduct of each line of compliance protection. The concept of three lines of protection is analyzed in detail, the cell is widely known in banking. Recommendations on its adaptation to the conditions of industrial enterprise are developed. The concept of the fourth line of compliance protection was formed and recommendations for its practical use in industrial enterprises were given.
Keywords: compliance; competitiveness; industrial enterprises